P-glycoprotein modulation by the designer drugs methylenedioxymethamphetamine, methylenedioxyethylamphetamine and paramethoxyamphetamine - Ketabi-Kiyanvash, Nahal; Weiß, Johanna; Haefeli, Walter E.; Mikus, Gerd (Addiction biology, 2003)
There are increasing numbers of deaths related to taking MDMA, MDE and PMA reported where the deceased typically took several different drugs with these compounds. Hence, mutual modulation of the pharmacokinetics in drug combinations with “ecstasy” might be a risk factor for “ecstasy”-related morbidity. Regarding potential drug-drug interactions, there are no data evaluating a possible contribution of the multidrug resistance transporter P-glycoprotein (Pgp) in contrast to the cytochrome P450 enzyme system. Therefore, individual “ecstasy” compounds have been tested for their ability to interact with Pgp using a fluorometric calcein assay as a model for Pgp inhibition in porcine kidney epithelial cells with overexpression of human Pgp (L-MDR1). All three compounds increased calcein retention in L-MDR1 cells in a concentration-dependent manner, with MDE being the most potent and MDMA the weakest Pgp inhibitor. The effective concentrations were 1-3 orders of magnitude higher than plasma concentrations observed in vivo, suggesting that these compounds are only weak inhibitors of Pgp, which is unlikely to influence the access of other compounds to the brain. However, it cannot be excluded that co-administration of Pgp inhibitors such as ritonavir or paroxetine could increase MDMA, MDE and PMA bioavailability and also enhance brain entry leading to severe side effects.
First published: 09 June 2006
Gesehen am 28.07.2021